PROBLEMATIKA PERNIKAHAN SIRI DI KECAMATAN PERAK KABUPATEN JOMBANG PADA ERA SOCIETY 5.0 - Fakhrurrozi, Azmirozi; Pradana, Sandi Yoga; Fauziyah, Ita Ma’rifatul; Saputro, Eko Andy (International Conference on Humanity Education and Society (ICHES), 2024)
According to Islamic law, marriage is considered a very strong form of bond or mitsaqon ghalidhan to obey Allah's commands, and carrying it out is an act of worship. Siri marriage can be defined as "a form of marriage that is carried out according to law or religious customs, is not announced in public and is not officially recorded in the marriage registry." marriage of 'public officials'. This article aims to examine the level of understanding of positive law regarding unregistered marriages. This research method is descriptive qualitative with documentary data collection techniques and descriptive analysis as a data analysis technique. Active legal research on unregistered marriages is carried out primarily based on the legal nature of the Republic of Indonesia and government regulations. The study of Islamic law regarding unregistered marriages is carried out based on the Al-Quran and Hadith. From the perspective of Indonesian positive law, law, unregistered marriage is a marriage that has no legal principles or in other words has no legal consequences.